2020
DOI: 10.1002/oby.22722
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Profiling in Adipose Before and After Weight Loss Highlights the Role of miR‐223‐3p and the NLRP3 Inflammasome

Abstract: Objective Adipose tissue plays a key role in obesity‐related metabolic dysfunction. MicroRNA (miRNA) are gene regulatory molecules involved in intercellular and inter‐organ communication. It was hypothesized that miRNA levels in adipose tissue would change after gastric bypass surgery and that this would provide insights into their role in obesity‐induced metabolic dysregulation. Methods miRNA profiling (Affymetrix GeneChip miRNA 2.0 Array) of omental and subcutaneous adipose (n = 15 females) before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(61 reference statements)
0
6
0
1
Order By: Relevance
“…have observed downregulation of miR-223-3p expression in the omentum and subcutaneous adipose tissue after weight loss induced by a gastric bypass (43) .…”
Section: Discussionmentioning
confidence: 95%
“…have observed downregulation of miR-223-3p expression in the omentum and subcutaneous adipose tissue after weight loss induced by a gastric bypass (43) .…”
Section: Discussionmentioning
confidence: 95%
“…Previous evidence shows that miR-223-3p is not only related to bone, but also with adipose tissue. Macartney-Coxson et al have observed downregulation of miR-223-3p expression in the omentum and subcutaneous adipose tissue after weight loss induced by a gastric bypass (43) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found an association between miR-223-3p and NLRP3 inflammatory hyperactivation in obesity for the first time. In subcutaneous fat, a significant correlation was observed between miR-223-3p and miR-223-5p and glucose, NLRP3, and blood lipids (Macartney-Coxson et al 2020 ). In another study, the expression levels of miR-223-3p and NLRP3 were measured in glioblastoma tumor tissue.…”
Section: Nlrp3 Inflammasome As a Potential Target For Mir-223mentioning
confidence: 99%